SOSIALISASI TERAPI JAHE(ZINGIBER OFFICINALE)TERHADAP PENURUNAN INTENSITAS KELUHAN LOW BACK PAIN - Rosita Ginting; Irmayani Irmayani; Anggi Isnani Parinduri; Fadlilah Widyaningsih; Ade Fitri Khairani (JURNAL PENGMAS KESTRA (JPK), 2021)
Low Back Pain is a very common world health problem, causing activity restrictions and loss of work attendance. The World Health Organization (WHO) states that the prevalence of LBP is around 60-80% and is the main cause of worker absenteeism from work and the cause of millions of lost working days each year. Ginger therapy can reduce complaints of pain felt in LBP patients. This PKM activity aims to provide socialization of ginger therapy (zinger officinale) to reduce the intensity of LBP complaints to angkot drivers at Lubuk Pakam area. The method used in this PKM activity uses a lecture technique with the media used, PPT, LCD, projector and leaflet. The target of this activity is angkot drivers in the Lubuk Pakam area, totaling 48 people. There was an increase in participants' knowledge before and after being given socialization about ginger therapy by 45.9%. Ginger therapy is effective for reducing LBP pain felt by angkot drivers in the Lubuk Pakam area.